ANALISIS PERENCANAAN SISTEM PEMBANGKIT LISTRIK HYBRIDE (PLTS DAN DIESEL) PADA KAPAL TANKER - Akbar, M Aidil; Tarigan, Amani Darma; Lesmana, Dicky (Power Elektronik : Jurnal Orang Elektro, 2024)
The hybrid power generation system (solar cells and diesel generator) is one of the alternative solutions to the negative impacts of conventional energy systems on ships in Indonesia. The use of this hybrid power generation system can support the development of environmentally friendly ship technology as global warming issues become more widespread. The advantages of implementing a hybrid power generation system include a reduction in fuel consumption by the generator and a simultaneous decrease in emissions from the ship. Choosing a hybrid system with solar power is particularly advantageous in Indonesia due to its abundant sunlight. This study employs technical and economic analytical methods to design a hybrid power generation system (solar cells and diesel generator). Technical and economic analyses are conducted using a tanker ship as the research object, comparing the hybrid power generation system with the conventional system widely used on ships in Indonesia. The research results indicate that the implementation of a hybrid power generation system on tanker ships results in a 15.5% annual fuel consumption saving compared to the use of conventional power generation systems. Therefore, due to the increased investment costs and reduced operational costs in the hybrid power generation system compared to the conventional system, the break-even point can be achieved in 3.69 years or equivalent to a total nominal cost of Rp 23,980,000,000.00 or $1,803,007.52.